2016
DOI: 10.1016/j.biochi.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 confers anti-inflammatory effects in acute liver injury via suppressing M1 macrophage polarization

Abstract: Protein interacting with C kinase 1 (PICK1) is a scaffolding protein mainly implicated in neurological diseases, however, the function of PICK1 in acute liver injury (ALI) remains unknown. Our study found a dramatical decrease in mRNA and protein levels of PICK1 in liver tissues and isolated Kupffer cells (KCs) from the liver in mice with ALI. Furthermore, pretreatment the mice with ALI with FSC-231, a pharmacological inhibitor of PICK1, could significantly augment inflammatory response. Furthermore, in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…In the study presented here, we found that ginsenoside Rg3 significantly inhibited the increases of the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 as well as prevented the decreases of anti-inflammatory cytokines IL-10 and TGF-β after LPS stimulation. The process by which macrophage activation induced different subtypes to respond to changes in the environment is generally called polarization, and the phenotype of polarization can be divided into M1 and M2 ( Xie et al, 2016 ). The polarization of M2 macrophages appears to promote the release of anti-inflammatory and immunosuppressive agents as well as motivate the repair and healing of damaged tissue ( Arnold et al, 2007 ; Kang et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study presented here, we found that ginsenoside Rg3 significantly inhibited the increases of the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 as well as prevented the decreases of anti-inflammatory cytokines IL-10 and TGF-β after LPS stimulation. The process by which macrophage activation induced different subtypes to respond to changes in the environment is generally called polarization, and the phenotype of polarization can be divided into M1 and M2 ( Xie et al, 2016 ). The polarization of M2 macrophages appears to promote the release of anti-inflammatory and immunosuppressive agents as well as motivate the repair and healing of damaged tissue ( Arnold et al, 2007 ; Kang et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PICK1 influences the progress of acrosome biogenesis, and its deficiency is accompanied by increased apoptosis [ 15 ]. PICK1 is also proved to have an anti-inflammatory role in LPS-induced acute liver injury by suppressing macrophage polarization [ 16 ]. A recent study showed that the failure of PICK1 localization to nucleus-associated acrosomic vesicles influences acrosome biogenesis in Sirtuin-1-deficient germ cells, and the progress was associated with disrupted autophagic flux [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This particular structure enables PICK1 to bind to various membrane proteins, thus initiating multiple functions [ 20 22 ]. PICK1 is widely expressed in various organs and has been found to participate in the oxidative regulation by regulating glutathione (GSH, an important antioxidant) [ 23 ] in the lung [ 24 ] and liver [ 25 ]. However, the research on the relationship between PICK1 and SA-AKI is relatively rare.…”
Section: Introductionmentioning
confidence: 99%